Analysis of trends in the production volumes of construction materials in Ukraine and Europe - Gayda, Serhiy (Forestry, Forest, Paper and Woodworking Industry, 2025)
The significance of the woodworking industry of the Ukrainian forest industry complex from the perspective of a circular economy is substantiated, since this economic model focuses on the implementation of its principles on the reduction of residues and waste, the comprehensive reuse of wood resources as a whole. The indicators of board production for the seven-year period (2018-2024) are analyzed with average production indicators for the following materials: wood-based particleboards (2267.00 thousand m3), oriented strand boards (152.14 thousand m3), medium-density fiberboard (MDF) (242.14 thousand m3), plywood (210.00 thousand m3) and veneer (220.14 thousand m3). The dynamics of particleboard production in Ukraine for the period from 2018 to 2024 are analyzed in detail. with growth and decline indices: 2018/2019 – 88.90%; 2019/2020 – 97.01%; 2020/2021 – 133.80%; 2021/2022 – 59.65%; 2022/2023 – 113.60%; 2023/2024 – 108.60%. The panel production indicators for the three-year period (2021-2024) for EU countries were analyzed with average production indicators for the following materials: particleboard (31.55 million m3), oriented strand board (6.83 million m3), medium-density fiberboard (MDF) (12.08 million m3), plywood (2.81 million m3). Ways of providing raw materials to the woodworking industry in the context of a circular economy are proposed, which consist, first of all, in the use of wood waste, as the main idea of a circular economy regarding the conversion of waste and residues into a resource for the creation of wood-based panel materials, such as chipboard, MDF and OSB, which undoubtedly saves natural resources. Trend lines were constructed and determination coefficients were obtained that characterize the state, dynamics and prospects of the production of wood-based structural panel materials in Ukraine: at high R² (0.8–0.95), the production of wood-based panels demonstrates a clear trend (growth or decline) without sharp deviations, which indicates the relative stability of the industry and predictability; at low R² (0.2–0.5), we receive signals of instability: perhaps the market is very sensitive to fluctuations in raw material prices, exchange rates or political risks. Thus, based on the obtained R², it is possible to clearly understand how reliable the analyzed trend model is and plan further analytical and management actions.